Modulation Of Vaginal Immune Response By Trichomonas Vaginalis With The Correlation Between Bacterial Vaginosis And Infertility - Das, Sourav; J. Pradeep, J. Pradeep; P. Lavanya, P. Lavanya; A.N. Uma, A.N. Uma (Journal of Neonatal Surgery, 2025)
Trichomonas vaginalis (T. vaginalis), a sexually transmitted protozoan, is a major contributor to genitourinary infections, often coexisting with bacterial vaginosis (BV). This parasitic infection not only induces inflammation but also modulates the host immune response, leading to significant reproductive health concerns, including infertility. The interplay between T. vaginalis and BV disrupts the vaginal microbiota, reducing Lactobacillus species and promoting the overgrowth of anaerobic bacteria such as Gardnerella vaginalis. This shift compromises vaginal immunity, allowing chronic infections that contribute to reproductive tract inflammation. T. vaginalis influences the immune system through various mechanisms, including antigenic variation, inhibition of neutrophil apoptosis, and suppression of Th1-mediated responses, leading to prolonged immune tolerance. These immunomodulatory strategies facilitate persistent infections and increase susceptibility to sexually transmitted infections (STIs), including HIV. The parasite also interacts with BV-associated bacterial biofilms, further impairing microbial clearance and exacerbating vaginal dysbiosis. The association between T. vaginalis, BV, and infertility is multifaceted. Chronic inflammation, cervical mucus alterations, and endometrial involvement create a hostile environment for sperm survival and embryo implantation. Additionally, T. vaginalis-induced pelvic inflammatory disease (PID) can lead to tubal scarring and ectopic pregnancies. Given these significant reproductive health implications, routine screening and treatment strategies should be prioritized, particularly in high-risk populations. Future research should focus on understanding the immune mechanisms underlying T. vaginalis and BV interactions to develop targeted therapeutic interventions aimed at mitigating infertility risks associated with these infections.